Carbon footprint of Li-Oxygen batteries and the impact of material and structure selection. (April 2023) - Chen-Glasser, Melodie; Landis, Amy E.; DeCaluwe, Steven C.
Abstract: High energy density lithium-O 2 batteries have potential to increase electric vehicle driving range, but commercialization is prevented by technical challenges. Researchers have proposed electrolytes, catalysts, and binders to improve the battery capacity and reduce capacity fade. Novel battery design, however, is not always consistent with reduction in greenhouse gas (GHG) emissions. Optimizing battery design using solely electrochemical metrics ignores variations in the environmental impacts of different materials. The lack of uniform reporting practices further complicates such efforts. This paper presents commonly used lithium-O 2 battery materials along with their GHG emissions. We use LCA methodology to estimate GHG emissions for five proposed lithium-O 2 battery designs: (i) without catalyst, (ii) with catalyst, (iii) carbon-less and binder-less, (iv) anode protection, and (v) carbon-less, binder-less with gold catalyst. This work highlights knowledge gaps in lithium-O 2 battery LCA, provides a benchmark to quantify battery composition impacts, and demonstrates the GHG emissions associated with certain materials and designs for laboratory-scale batteries. Predicted GHG emissions range from 10–70 kg of CO 2 equivalent (kg CO 2 e ) kg −1 of battery, 60–1200 kg CO 2 e kWh −1, and 0.15–21 kg CO 2 e km −1 of vehicle travel, if battery replacement is considered. Highlights: GHG emissions for lithium-oxygen battery materials are compiled and reported. Lithium-oxygen battery material choice has a significant impact on GHG emissions. High emission materials may negate GHG reductions from improved battery performance. Carbon footprints should be incorporated to guide battery material choices. Battery reporting should be standardized to support carbon footprint analysis.